The impact of the lesson study model on students' mathematics achievement and attitudes: a mixed-methods research - Aykan, Ahmet (Emerald Group Publishing Ltd, 2024)
Purpose- This article aims to investigate the impact of the Lesson Study (LS) model on students' mathematics achievement and attitudes toward mathematics. Design/methodology/approach- The study employs a concurrent embedded design, a type of mixed methods design. Within this framework, a quantitative pretest-posttest control group quasi-experimental design is applied for quantitative data, while qualitative data is gathered through interviews and observations. A 2x2 mixed ANOVA is used for the analysis of quantitative data, and content analysis is employed for qualitative data analysis. Findings- The findings reveal that the LS model has a significant positive impact on the mathematics achievement and attitudes of students in the experimental group. Quantitative analysis shows a meaningful improvement in mathematics achievement for the experimental group, which is notably superior than the control group. Additionally, students in the experimental group found mathematics lessons more enjoyable and easier, and their attitudes toward mathematics improved positively. Students' feedback supports these results, with many expressing that LS-based lessons were more engaging and effective. Observations by the researcher, mathematics expert and teacher in the experimental group also corroborate these positive changes. Originality/value- The results of the study suggest that the LS model should be more widely implemented in mathematics education. This recommendation highlights the potential of the LS model to enhance the teaching process and improve students' mathematics achievement. Furthermore, the study also indicates that LS has a positive impact on students' attitudes toward mathematics, as evidenced by their increased motivation and more positive outlook toward the subject. These findings underscore the LS model's effectiveness in both improving academic performance and transforming students' attitudes toward mathematics.
Keywords: Lesson study; Mathematics achievement; Attitude toward mathematics; Mixed-methods